2019
DOI: 10.20892/j.issn.2095-3941.2018.0506
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and clinical significance of pathogenic germline BRCA1/2 mutations in Chinese non-small cell lung cancer patients

Abstract: Objective: Germline alterations in the breast cancer susceptibility genes type 1 and 2, BRCA1 and BRCA2, predispose individuals to hereditary cancers, including breast, ovarian, prostate, pancreatic, and stomach cancers. Accumulating evidence suggests inherited genetic susceptibility to lung cancer. The present study aimed to survey the prevalence of pathogenic germline BRCA mutations (gBRCAm) and explore the potential association between gBRCAm and disease onset in Chinese advanced non-small cell lung cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 29 publications
5
20
0
Order By: Relevance
“…3 Recently, an association between BRCA2 and lung cancer was suggested in a large Chinese study with a 0.8% PV prevalence in patients with advanced non–small-cell lung cancer. 4 Furthermore, a recent study concluded that lung cancer occurred significantly earlier in BRCA2 PVs carriers compared with noncarriers by approximately 12 years (95% CI, 2.5 to 20.6). 5 In conclusion, an impact of germline BRCA2 PV on lung cancer risk remains open for discussion.…”
Section: To the Editormentioning
confidence: 99%
“…3 Recently, an association between BRCA2 and lung cancer was suggested in a large Chinese study with a 0.8% PV prevalence in patients with advanced non–small-cell lung cancer. 4 Furthermore, a recent study concluded that lung cancer occurred significantly earlier in BRCA2 PVs carriers compared with noncarriers by approximately 12 years (95% CI, 2.5 to 20.6). 5 In conclusion, an impact of germline BRCA2 PV on lung cancer risk remains open for discussion.…”
Section: To the Editormentioning
confidence: 99%
“…The authors wrote "accumulating evidence suggests inherited genetic susceptibility to lung cancer." 7 As further evidence of BRCA PGVs predisposing to NSCLC, the authors noted in their report that patients with NSCLC and a PGV tended to be younger than those not carrying a PGV. 7 Tian et al reported that among 1764 patients with lung cancer (97% with NSCLC), 67 (3.8%) were found to have a PGV/likely pathogenic variant (LV), with BRCA2 being the most common PGV identified (0.79%).…”
Section: Discussionmentioning
confidence: 93%
“…7 As further evidence of BRCA PGVs predisposing to NSCLC, the authors noted in their report that patients with NSCLC and a PGV tended to be younger than those not carrying a PGV. 7 Tian et al reported that among 1764 patients with lung cancer (97% with NSCLC), 67 (3.8%) were found to have a PGV/likely pathogenic variant (LV), with BRCA2 being the most common PGV identified (0.79%). 8 Among 1026 NSCLC patients, Liu et al suggested "plausible" susceptibility from germline variants in 4.7%, again with the most common PGV identified being BRCA2.…”
Section: Discussionmentioning
confidence: 93%
“…Studies other than the two presented in the introduction [7,8] have found an unusually high prevalence of BRA1/2gl variants among LC patients. In a national Chinese multicenter retrospective study conducted in advanced stage (stage III-IV) non-small cell lung cancer (NSCLC), Hu et al [10] found a 1.03% (64 of 6220 participants) prevalence of BRCA1/2glpv which was higher than the estimated frequency in East Asians (0.2%) [11]. In a recent crosssectional study including 7768 LC patients, the prevalence of BRCA2glpv [12] was 0.66%.The SAFIR02-Lung trial [13] is a French multi-center, open-label, randomized, phase II adaptative trial investigating untreated advanced NSCLC wild-type for EGFR and ALK.…”
Section: Discussionmentioning
confidence: 99%